2016
DOI: 10.1002/jssc.201501315
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous qualitative and quantitative analysis of flavonoids and alkaloids from the leaves of Nelumbo nucifera Gaertn. using high‐performance liquid chromatography with quadrupole time‐of‐flight mass spectrometry

Abstract: A reliable method, combining qualitative analysis by high-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry and quantitative assessment by high-performance liquid chromatography with photodiode array detection, has been developed to simultaneously analyze flavonoids and alkaloids in lotus leaf extracts. In the qualitative analysis, a total of 30 compounds, including 12 flavonoids, 16 alkaloids, and two proanthocyanidins, were identified. The fragmentation behaviors of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Five quercetin analogs shared fragment ions at m/z 303, while three kaempferol analogs shared fragment ions at m/z 284/285. These fragment ions and this fragmentation pattern of quercetin and kaempferol derivatives fit well with previous reports on flavonol derivatives in herbs that contain SLT [ 16 , 36 ]. Phytochemical and spectroscopic studies on herbs containing SLT suggested that quercetin and kaempferol derivatives were the most abundant metabolites [ 11 , 16 , 17 , 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…Five quercetin analogs shared fragment ions at m/z 303, while three kaempferol analogs shared fragment ions at m/z 284/285. These fragment ions and this fragmentation pattern of quercetin and kaempferol derivatives fit well with previous reports on flavonol derivatives in herbs that contain SLT [ 16 , 36 ]. Phytochemical and spectroscopic studies on herbs containing SLT suggested that quercetin and kaempferol derivatives were the most abundant metabolites [ 11 , 16 , 17 , 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, two more flavonoids (peaks 91 and 93) were found in G. orientalis . On the one hand, the MS data and the aglycone ion corresponding to kaempferol ( m / z 285) allowed us to identify peak 91 (m/z 461) as kaempferol‐ O ‐β‐ d ‐glucuronide which has been described in other plants . On the other hand, a flavonoid with molecular formula C 28 H 36 O 15 (peak 93) was identified as hesperidin dihydrochalcone (Figure D).…”
Section: Resultsmentioning
confidence: 81%
“…9,35 In this regard, the fragmentation pattern of rossicadide A is shown in Figure 2 plants. 44 On the other hand, a flavonoid with molecular formula C 28 H 36 O 15 (peak 93) was identified as hesperidin dihydrochalcone ( Figure 2D). The last new compound identified in the samples under study was earlier described in other leaves 45 and has been tentatively characterised as 4H-1-benzopyran-4-one, 3,7-bis[(O-acetyl-6deoxy-α-L-mannopyranosyl)oxy]-2-(4-ethoxyphenyl) ( Figure 2E).…”
Section: Phenylethanoid Glycosidesmentioning
confidence: 99%
“…Lotus leaves are dry leaves of the Nelumbo nucifera Gaertn, which is a well known traditional Chinese medicine and has functions such as clearing away the heat and dampness, preventing hair loss and promoting hair growth, cooling the blood, and hemostasis [6,7]. Modern medical studies have revealed that the main active components of lotus leaves are flavonoids and alkaloids [8,9]. Currently, the flavonoids in lotus leaves have been reported to reduce the blood lipid level, to have anti-allergy, anti-cancer, anti-aging, bacteriostatic, and anti-oxidation functions, and to be helpful in treating cardiovascular diseases [10,11].…”
Section: Introductionmentioning
confidence: 99%